787 THE PRUNE PROJECT: USING PRUNES AS A CONSTIPATION AID IN OLDER SURGICAL INPATIENTS. (8th March 2022) - Coath, F; Morgan, C
Abstract: Introduction: Constipation is a common and difficult issue in elderly surgical patients, often contributing to prolonged stay on inpatient wards (Sethi et al, Am J Gastroenterol. 2014;109:250–256). Increasing dietary fibre is a commonsense tactic to mitigate against constipation. However it is rarely formally employed on NHS wards. Prunes are beneficial in increasing fibre intake and are a natural source of sorbitol, which acts as an osmotic laxative (Stacewicz-Sapuntzakis et al, Crit Rev Food Sci Nutr. 2001;41:251–86.) Method: We performed a closed-loop audit on the use of prunes in reducing constipation. We collected data from surgical inpatients over 60 years, including the number of days since bowels were last opened, and the number of laxatives that each patient was taking. Patients were then given a prune product (either 3 dried prunes, 125 mL prune juice or 70 g prune puree) three times a week. Following the intervention, the data was recollected to complete the audit cycle. Results: In our cohort of 36 patients, the mean time since bowels were last opened reduced from 1.49 to 1.17 days (p = 0.1624) after introducing prunes three times a week, and the mean number of laxatives reduced from 1.81 to 1.50 (p = 0.1671). Conclusion: Surgical patients are at increased risk of constipation (Davies et al, J Clin Pharm Ther. 2008; 31:561–566) due to multiple factors including immobility, poor oral intake and opiate use. Constipation is more common in the elderly (Talley et al, Am J Gastroenterol. 1996;91:19–25), who are also at increased risk of polypharmacy (Morin et al, Clin Epidemiol. 2018;10:289–298). These results show that using prunes to aid regular bowel motion can have a positive impact on reducing pharmacy and increasing frequency of bowels opening. We hope that, by introducing tactics to promote regular bowel motions in hospital, we can reduce polypharmacy and instill good health habits post-discharge.